MARKETING STRATEGY ANALYSIS USING SWOT (STRENGTH WEAKNESS OPPORTUNITY THREAT) AT CAFE FOX COFFEE & ROASTERY JEMBER - Reza Ardiansyah; Haifa Haifa; Hayatul Masfufah (LPPM Institut Teknologi dan Sains Mandala, 2021)
This study aims to determine the marketing strategy at Fox Coffee & Roastery Jember cafe, using a SWOT analysis (strength weakness opportunity threat). The data used in this study are primary data and secondary data. This research uses qualitative research. Methods of data collection using observation, interviews, documentation, questionnaires, and literature study. The sample used in this study was purposive sample. The resource persons taken in this study were company managers and 15 consumers of Fox Coffee & Roastery Jember cafe. Methods of data analysis using the IFE matrix, EFE matrix and SWOT matrix. The results of this study indicate that the marketing strategy used by Fox Coffee & Roastery Jember cafe is an aggressive strategy. This can be proven by the high score on the table of strength (strength) and opportunity (opportunity) owned by the cafe. So, Fox Coffee & Roastery Jember cafe has the potential to become a cafe that can dominate the market in Jember itself. Keywords: Strength, weakness, opportunity, threats, and marketing strategies